1997
DOI: 10.1007/pl00005024
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chronic treatment with fluoxetine and citalopram on 5-HT uptake, 5-HT1B autoreceptors, 5-HT3 and 5-HT4 receptors in rats

Abstract: The effect in rats of chronic treatment with two specific 5-HT reuptake inhibitors (SSRI) with antidepressant properties, citalopram (10 mg/kg, i.p. twice a day for 14 days, one day washout) and fluoxetine (15 mg/kg, p.o. twice a day for 21 days, 7 days washout), was evaluated on some mechanisms involved in central 5-HT neurotransmission. No adaptive modifications of brain 5-HT uptake (sites) were found by measuring functional [3H]5-HT uptake and [3H]citalopram binding in cortical and hippocampal synaptosomes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 2 publications
1
34
1
1
Order By: Relevance
“…This interpretation is in accordance with our observation of a high interregional correlation of 5-HT 2A receptor binding, which is suggestive of a common regulator, presumably the raphe serotonergic output. Given that the 5-HT 2A receptor binding is accepted as a surrogate marker of cerebral 5-HT levels and that SERT binding adjusts to 5-HT levels in a manner suggested from some, although not all, experimental studies (Graham et al, 1987;Kovachich et al, 1992;Cheetham et al, 1993;Pineyro et al, 1994;Rattray et al, 1996;Gobbi et al, 1997;Benmansour et al, 1999;Horschitz et al, 2001;Benmansour et al, 2002;Evrard et al, 2002;Gould et al, 2003Gould et al, , 2006Rothman et al, 2003), our observation of an inverted U-shaped relation between 5-HT 2A receptor and SERT binding may be the result of inter-individual differences in cerebral baseline 5-HT levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This interpretation is in accordance with our observation of a high interregional correlation of 5-HT 2A receptor binding, which is suggestive of a common regulator, presumably the raphe serotonergic output. Given that the 5-HT 2A receptor binding is accepted as a surrogate marker of cerebral 5-HT levels and that SERT binding adjusts to 5-HT levels in a manner suggested from some, although not all, experimental studies (Graham et al, 1987;Kovachich et al, 1992;Cheetham et al, 1993;Pineyro et al, 1994;Rattray et al, 1996;Gobbi et al, 1997;Benmansour et al, 1999;Horschitz et al, 2001;Benmansour et al, 2002;Evrard et al, 2002;Gould et al, 2003Gould et al, , 2006Rothman et al, 2003), our observation of an inverted U-shaped relation between 5-HT 2A receptor and SERT binding may be the result of inter-individual differences in cerebral baseline 5-HT levels.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro autoradiography and homogenate binding experiments in rats suggest that a decrease in SERT binding levels occur after pharmacologically induced chronic extracellular 5-HT depletion in two (Rattray et al, 1996;Rothman et al, 2003) of three studies (no change seen in the study by Dewar et al, 1992). Chronically elevated extracellular 5-HT levels have usually been achieved by chronic treatment with the specific selective serotonin reuptake inhibitor (SSRI) compounds sertraline, citalopram, and paroxetine, and, in 10 ( Kovachich et al, 1992;Pineyro et al, 1994;Benmansour et al, 1999;Horschitz et al, 2001;Benmansour et al, 2002;Gould et al, 2003Gould et al, , 2006Rossi et al, 2008) of 15 experimental settings (no change reported in the studies by Graham et al, 1987;Kovachich et al, 1992;Cheetham et al, 1993;Gobbi et al, 1997;Gould et al, 2006), decreased SERT levels have been found. It can be argued, however, that chronic blockade of the SERT may lead to regulation of its expression and that the primary cause for the SERT downregulation is unrelated to 5-HT levels.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, there is evidence that the persistent increase in extracellular 5-HT induced by chronic fluoxetine might be explained by the desensitisation of terminal 5-HT 1B autoreceptors, whose activation exerts a feedback inhibition of 5-HT release, as demonstrated by electrophysiology and microdialysis assays [42,43]. Accordingly, the support for fluoxetine-induced 5-HT 1B subsensitivity came from the decrease in receptor expression observed [44], although other reports did not confirm this effect [36,45]. Other explanations of the mechanism of action of fluoxetine after long-term treatment have also been proposed.…”
Section: Long-term Fluoxetinementioning
confidence: 99%
“…For example, the role of other 5-HT receptors has been evoked, given that chronic fluoxetine treatment also downregulates the density of 5-HT 4 receptors and produces a functional desensitisation involving the adenylate cyclase system [46]. By contrast, long-term treatment does not provoke robust alterations in other 5-HT receptors, such as 5-HT 2 or 5-HT 3 [45,47,48]. In addition, there is some controversy regarding the role of 5-HT transporters in the adaptive changes following chronic fluoxetine administration [36,38,44].…”
Section: Long-term Fluoxetinementioning
confidence: 99%
“…20 However, the literature on the effects of long-term antidepressants on the serotonin transporter (SERT) or norepinephrine transporter (NET) are inconsistent. [21][22][23][24][25][26][27] We decided to re-examine this issue, and speculated that two factors needed to be addressed in our studies. One was how the drugs are administered.…”
Section: Effects On Serotonergic Transportersmentioning
confidence: 99%